Exploring new territory: an initial investigation into the potential of a formal industry capacity building programme to shift values among Cape Town paratransit operators - Van Aardt, Camilla Elizabeth (School of Management Studies, 2019)
Organisational Psychology’s focus on the formal business setting has resulted in the discipline limiting its potential contribution to and relevance in broader society. To address this shortfall this study was conducted in the paratransit industry, which is the largest contributor to the informal economy in South Africa. It is based on the argument that by applying discipline specific knowledge, Organisational Psychology may have the potential to assist in transforming the culture in the paratransit industry, a culture which has been described as violent, aggressive and undemocratic. As culture can shift through industry-leader driven changes in values, the first step was to understand what values are held by leaders within the paratransit industry. The second step was to find ways in which to shift values. Using Schwartz’s (1992) Theory of Basic Human Values as theoretical framework, this dissertation consequently served to surface the values among paratransit operators which may underlie the violent and aggressive culture in the Cape Town paratransit industry. Secondly, it sought to determine if value shifts may be achieved through formal business skills capacity training. To this end, the extent to which paratransit operators who had participated in such a training programme demonstrated different values to non-participant paratransit operators was assessed. By employing a quasi-experimental post-test design participants (n = 46) and non-participants (n = 46) in a particular three-year capacity-building programme responded to Schwartz et al.’s (2001) Portrait Values Questionnaire (PVQ), which assesses the universal value dimensions stipulated by Schwartz (1992), as well as to additional scales assessing trust in the City of Cape Town (CoCT) and Transport for Cape Town (TCT). The sample valued universalism, benevolence, conformity and security – values that are not generally associated with violent, aggressive and undemocratic behaviour. Power, on the other hand, was neither valued nor not valued although it had been expected to be espoused strongly. The only result in line with expectations was that participants valued stimulation to some extent. Participants indicated trust in the CoCT and TCT. While training participants and non-participant paratransit operators did not differ significantly in the degree to which they espoused the different values and their degree of trust in the two transport authorities, the effect sizes for the differences in conformity, power, security, and universalism as well as trust in the two transport authorities were meaningful. It needs to be noted, though, that a number of limitations in the study design, particularly that no pre-intervention data was available, means that it is not possible to assess if the values of paratransit operators had shifted over the duration of the programme. Consequently, one cannot be certain that such a programme is an effective means of shifting espoused values. If, however, the values espoused by participants in this study are a reflection of reality, then paratransit operators endorse values that lend themselves to the formation of a non-aggressive and democratic culture. Organisational psychologists can assist in bringing about a positive shift to the operating culture of the paratransit industry by translating these value-conform behaviours shown towards drivers and by encouraging similar behaviour in their work and over time, these minibus-taxi drivers may shift their values and behaviours in turn. From a theoretical perspective, the findings on the dimensionality of the PVQ in the sample suggest that even though Schwartz (1992) assumed the value dimensions in the Theory of Human Values to be universal, what indicates each of these value dimensions is context dependent. This calls into question the universal applicability of the PVQ as a measurement tool for these values. The relative endorsement of value dimensions in relation to each other, however, was found to be in line with Schwartz’s (1992) assumptions.